2004
DOI: 10.1002/jsfa.1635
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and in vitro digestibility of some Spanish browse plant species

Abstract: Samples of leaves, flowers and fruits of four browse species were collected from uplands in the province of León (northwestern Spain) at different sampling times (from spring till autumn). The browse species were Erica australis (Spanish heath), Cistus laurifolius (laurel-leaved rock rose), Quercus pyrenaica (hoary oak) and Rosa canina (wild dog rose). A large variability in chemical composition and in vitro digestibility and gas production kinetics was observed among species and among sampling times within ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
29
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 37 publications
12
29
1
3
Order By: Relevance
“…The CP contents in samples suggest that Crataegus leaves have the advantage of maintaining their nutritive value throughout the dry season. The CP, NDF and ADF levels in the leaves, seeds and fruits to R. canina were similar to the findings of Ammar et al (2004). Previous studies reported low levels of CP (< 100 g·kg -1 DM) in the leaves of some browse plants, especially at mature stages (Tolera et al, 1997;Paton et al, 1999;González-Hernández and Silva-Pando, 2009).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The CP contents in samples suggest that Crataegus leaves have the advantage of maintaining their nutritive value throughout the dry season. The CP, NDF and ADF levels in the leaves, seeds and fruits to R. canina were similar to the findings of Ammar et al (2004). Previous studies reported low levels of CP (< 100 g·kg -1 DM) in the leaves of some browse plants, especially at mature stages (Tolera et al, 1997;Paton et al, 1999;González-Hernández and Silva-Pando, 2009).…”
Section: Discussionsupporting
confidence: 83%
“…In the current experiment, in vitro gas production of the Rosaceae fruit mixture was positively correlated with the CP content, similarly as found by Menke and Steingass (1988). Ammar et al (2004) stated that in vitro gas production after 24 h of incubation was determined at about 35 ml· 200 mg -1 DM for R. canina leaves and about 33 ml· 200 mg -1 DM for R. canina fruits. The results of Ammar et al (2004) are similar with the in vitro gas production results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The lowest value of IVDMD was found in Diet-AM because of its high content of fibre. This result was consistent with the finding of SeresinheandIben (2003); Ammar et al (2004); Njiddaand Nasiru (2010). They indicated that forage digestibility is mainly affected by the cell wall contents (NDF and ADF) and its lignifications.…”
Section: Methodssupporting
confidence: 92%
“…Most of smallholder dairy farmers in Myanmar have been used the conventional diets for their dairy cows, however the efforts concerning the determination of nutritive values of those diets were still limited. Chemical composition, in combination with in vitro gas production, OMD and ME content were widely used to determine the potential nutritive value of feedstuffs which are previously limited or uninvestigated (Ammar et al, 2004;Kaya et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…El incremento en los parámetros de producción de gas in vitro debido de la adición de PEG, fortalece los resultados obtenidos en previas investigaciones, resaltando la afinidad del PEG para neutralizar los TC (Khazaal et al, 1996) y la efectividad de la técnica para detectar la presencia de compuestos secundarios en las plantas arbustivas, como los TC (Ammar et al, 2004).…”
Section: Chemical Compositionunclassified